2007
DOI: 10.1007/s10856-006-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro apatite formation on polyamide containing carboxyl groups modified with silanol groups

Abstract: Modification of organic polymer with silanol groups in combination with calcium salts enables the polymer to show bioactivity, that is, the polymer forms apatite on its surface after exposure to body environment. However, how modification with silanol groups influences ability of apatite formation on the polymer substrate and adhesive strength between polymer and apatite is not yet known. In the present study, polyamide containing carboxyl groups was modified with different amounts of silanol groups, and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Therefore, it is concluded that in addition to providing additional oxygen atoms, which reduce the N c , the −OH groups play a far more significant role in terms of the bioactivity even at relatively low concentrations. This is in agreement with studies of apatite deposition on titanium that has been modified to have high concentrations of Ti-OH [44] at the surface and polymers with high concentrations of surface −COOH groups [45].…”
Section: (C) Atomic Structure Of Sol-gel-derived Bioactive Glasssupporting
confidence: 91%
“…Therefore, it is concluded that in addition to providing additional oxygen atoms, which reduce the N c , the −OH groups play a far more significant role in terms of the bioactivity even at relatively low concentrations. This is in agreement with studies of apatite deposition on titanium that has been modified to have high concentrations of Ti-OH [44] at the surface and polymers with high concentrations of surface −COOH groups [45].…”
Section: (C) Atomic Structure Of Sol-gel-derived Bioactive Glasssupporting
confidence: 91%
“…One method is to functionalize the biomaterial surface with reactive groups like Si-OH [29], Ti-OH [30], COO- [31], -SO 3 H [32] that would provide nucleation sites for apatite formation. In this regard, some functional groups might be more potent than others in their ability to nucleate apatite crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, surface engineering of polymers is an interesting way to modify the material and biological responses [12]. There have been several ways to improve the bioactivity of PA for bone repair, such as compounding with bioactive inorganic particles [8,13], grafting with bioactive groups [14] and forming bioactive coatings [5,15]. Compared with the first two methods, bioactive coating is a relatively facile and low-cost technique.…”
Section: Introductionmentioning
confidence: 99%